Bibliometric mapping of anemia in geriatric surgery - Can, Kubra; Taylan, Secil; Ozdere, Baris; Aslan, Fatma Eti (Elsevier, 2025)
Objective: In this study, scientific literature on anemia in geriatric surgical patients was reviewed using bibliometric analysis. Trends, scientific collaborations, and research gaps were identified. Method: On March 1, 2025, 640 articles were included in the analysis after searching the Web of Science database using MeSH terms such as geriatrics, elderly, surgery, anaemia anemia. Bibliometric evaluation was performed using the Biblioshiny interface. Publication years, authors, journals, keywords, countries, and collaborations were analyzed. Results: A total of 3376 authors took part in 640 articles published between 1984 and 2025. The average number of citations per article was 9.54. BMJ Case Reports and International Journal of Surgery Case Reports had the highest number of publications. According to Keywords Plus analysis, the most common terms were management, surgery, mortality and diagnosis. Discussion: This study examined the literature on anemia in elderly surgical patients using a bibliometric method and analyzed the research trends, collaborations, and knowledge structure in this field using the Web of Science database. This study highlighted the negative effects of anemia on surgical outcomes, identified gaps in the literature, and provided recommendations for future research. These findings provide a comprehensive assessment of the field in accordance with the interdisciplinary and complex nature of the subject. Conclusion: Key dynamics and gaps in the field were identified. In particular, significant research gaps were identified, including a lack of international collaboration, inadequate multidisciplinary approaches, and limited publications in some thematic areas (e.g., frailty and blood transfusion protocols). These findings can guide future, more comprehensive, and collaborative studies targeting these gaps.
Keywords: Geriatric surgery; Anemia; Bibliometric analysis; Old age